2012
DOI: 10.1155/2012/781375
|View full text |Cite
|
Sign up to set email alerts
|

Syk/Src Pathway-Targeted Inhibition of Skin Inflammatory Responses by Carnosic Acid

Abstract: Carnosic acid (CA) is a diterpene compound exhibiting antioxidative, anticancer, anti-angiogenic, anti-inflammatory, anti-metabolic disorder, and hepatoprotective and neuroprotective activities. In this study, the effect of CA on various skin inflammatory responses and its inhibitory mechanism were examined. CA strongly suppressed the production of IL-6, IL-8, and MCP-1 from keratinocyte HaCaT cells stimulated with sodium lauryl sulfate (SLS) and retinoic acid (RA). In addition, CA blocked the release of nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Although the exact mechanism of CA on excess cytokine release in obesity is not fully understood, CA has been shown to inhibit NF‐ κ B activation. In keratinocyte HaCat cells, CA suppressed NF‐ κ B activation by blocking its upstream signals including Syk/Src, phosphoinositide 3‐kinase (PI3K), Akt, inhibitor of κ B α (I κ B α ) kinase (IKK) and I κ B α . CA induced apoptosis of human prostate carcinoma cells through the activation of serine/threonine protein phosphatase 2A (PP2A) by modulating the Akt/IKK/NF‐ κ B pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of CA on excess cytokine release in obesity is not fully understood, CA has been shown to inhibit NF‐ κ B activation. In keratinocyte HaCat cells, CA suppressed NF‐ κ B activation by blocking its upstream signals including Syk/Src, phosphoinositide 3‐kinase (PI3K), Akt, inhibitor of κ B α (I κ B α ) kinase (IKK) and I κ B α . CA induced apoptosis of human prostate carcinoma cells through the activation of serine/threonine protein phosphatase 2A (PP2A) by modulating the Akt/IKK/NF‐ κ B pathway .…”
Section: Discussionmentioning
confidence: 99%
“…CA manifests significant protective effects in a cerebral artery occlusion model in mice (10), ameliorates obesity and hepatic steatosis in ob/ob mice [88, 89], inhibits microglial activation by lipopolysaccharide [90], inhibits adipocyte differentiation of 3T3-L1 cells [42], and abates light-induced retinal degeneration in rats [91]. In addition, CA and CS have been reported to display beneficial effects against acute and chronic inflammation, cardiovascular diseases, obesity, and cancer [94, 95], inhibition of prostaglandin synthesis [96], skin inflammation [97], p38 protein kinase activation [98], antiangiogenesis [99], protection against cisplatin [100], induction of neurotrophins [101], protection in an Alzheimer’s disease model [102], inhibition of NF-κB [103], inhibition of 5-lipoxygenase [104] and protection against dieldrin-induced degeneration of dopaminergic neurons [105]. For these reasons, we expect there to be intense activity in the coming years in an attempt to move these compounds or similar agents into clinical trials of specific patient populations, particularly for the CNS.…”
Section: (14) Potential For Carnosic Acid (Ca)/carnosol (Cs) In Clinimentioning
confidence: 99%
“…Although Ac-EE can strongly suppress Src and Syk, it is not yet clear which compounds act as active components in this extract. Recently, we found that CA is able to block both Src and Syk (Oh et al, 2012). Based on an HPLC finger printing assay, this extract was demonstrated to have similar types of diterpene compounds.…”
Section: Resultsmentioning
confidence: 94%